2019
DOI: 10.1002/solr.201900200
|View full text |Cite
|
Sign up to set email alerts
|

Organic‐Inorganic Halide Perovskites: From Crystallization of Polycrystalline Films to Solar Cell Applications

Abstract: In recent years, tremendous research interest has been devoted to organic–inorganic halide perovskites because of their excellent optical and electrical properties, which make them intriguing photovoltaic materials. The recorded efficiency of Pb‐based halide perovskite solar cells (PSCs) has gone beyond 24%, thus fulfilling their potential for industrialization. The photovoltaic performance of PSCs is predominantly determined by the quality of the perovskite film, which in turn, is controlled by the fabricatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 222 publications
(240 reference statements)
0
41
0
Order By: Relevance
“…It has been reported that the film fabrication method and film quality (surface uniformity, crystallinity, phase purity) play a critical role in device performance. 22 Moreover, the polycrystalline perovskite films suffer from severe instabilities arising the from morphological disorder at grain boundaries and surface degradation under ambient conditions, which can increase the recombination of the excited carriers. 23 , 24 In turn, perovskite single crystals (SCs) have been demonstrated to surmount these challenges because of exceptional optoelectronic properties such as low trap density, low intrinsic carrier concentration, high mobility, and long diffusion length.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the film fabrication method and film quality (surface uniformity, crystallinity, phase purity) play a critical role in device performance. 22 Moreover, the polycrystalline perovskite films suffer from severe instabilities arising the from morphological disorder at grain boundaries and surface degradation under ambient conditions, which can increase the recombination of the excited carriers. 23 , 24 In turn, perovskite single crystals (SCs) have been demonstrated to surmount these challenges because of exceptional optoelectronic properties such as low trap density, low intrinsic carrier concentration, high mobility, and long diffusion length.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Among these strategies, morphology engineering of the active perovskite layer has emerged as a promising route towards enhancing the film crystallinity and performance of the resulting devices. [4][5][6][7] Although in the field of photovoltaics the use of polycrystalline perovskite layers can still yield cells with high power conversion efficiency, [8] the situation is…”
Section: Doi: 101002/adma202003137mentioning
confidence: 99%
“…However, the V oc values of the prepared devices compared to the bandgap and reported studies are still very low. This may be because the coverage of the perovskite film fabricated via doctor blading still contains trance amounts of pinholes, which degrade V oc [30,31]. The solvent extraction due to the heat treatment is not as efficient as the antisolvent route in spin coating.…”
Section: Optimization Of Coating Temperaturementioning
confidence: 99%